Problem-based Learning: Developing Students' Critical Thinking - Raynesa Noor Emiliasari; Eka Prasetyo; Eva Fitriani Syarifah (Linguists : Journal Of Linguistics and Language Teaching, 2019)
The Problem-based Learning model is one of the learning models that can develop students’ critical thinking because it uses real-life problems foundation of learning activity. This research aims to describe the implementation of PBL in English language learning in developing students’ critical thinking, teacher’s role in PBL, teacher’s barriers and the impact of PBL toward students’ critical thinking. This research took place in one of the senior high school in Majalengka. The observation was conducted three times in the class of eleventh grade and then the interview was delivered to one English teacher. The result of the research reveals 1) PBL in English language learning begins with the teacher delivered the problem to the students as the foundation of learning activity and the problem was ill-structured and need deep analysis to formulate the solution; 2) teacher’s role is only as facilitator and co-investigator by providing situation to the students and help them in analysis; 3) time allocation, teacher’s capability and students’ speaking ability are the barriers in implementing PBL in English language learning; and 4) PBL develops students’ critical thinking skill, it can be seen through students characteristic which are elementary clarification, basic support, inference, advanced clarification and strategy and tactic.